Mental interference in orphanage children: public health literacy for children at orphanage - Sintya Clara, Ayu (BKM Public Health and Community Medicine, 2021)
Mental health problems are prone to occur in adolescents who are orphaned and live in orphanages. Children / adolescents living in orphanages are at a higher risk of exposure to various emotional disorders, such as depression, anxiety and stress, as well as behavioral problems than children or adolescents who are raised in their own family. Although orphans get substitute parents (caregivers), different from the role of biological parents, children will be more open to people who are close and live with them. Because he lost his biological parents, he was taken to an orphanage by his family, then after that no one ever visited him, making the child feel abandoned. This condition will make children become closed, alone and make it difficult to adapt to their peer environment. Some children do not want to hang out / be friends with someone they think is strange, eventually the orphan is marginalized and gets bullying which can lead to depression and even suicide attempts.